Food insecurity and nutritional outcome in children and mothers of Bangladesh and some perceptions to overcome malnutrition - Rabiul Islam, G,M; Jeroen, Buysse (Universiti Kebangsaan Malaysia, 2012)
To understand the extent of food insecurity in Bangladesh emphasizing on the non cereal food availability and maternal and child nutritional outcome. Methods We conducted systematic review in between 1985 to 2010 by using PubMed and Google Scholar databases as well as archives of relevant journals by hand. Contacting with the author was also performed in the case where original data needed. Results & Conclusions Results from the evidence it may be sated that despite the growth of cereal production and its availability Bangladesh is still problems with accessing of non cereal foods (e.g., vegetable, fruits, fish, milk, meat, egg etc) as well as the incidence of acute malnutrition in children and mothers were hardnosed in the rural area of Bangladesh.